Studies of Madagascan Ptiliidae (Coleoptera) 2: The genus Ptenidium including three new species - Darby, Michael (Zootaxa, 2014)
This is the second report detailing Ptiliidae collected from forest leaf litter by the Moravian Museum expeditions to Madagascar 2010–2012. 3 new species are described and figured: Ptenidium azafady sp. n., P. lambdai sp. n., and P. tanalai sp.n., and the criteria for assessing subgeneric status discussed.